Positive attitudes toward SMS advertising among generation Y in Kelantan/ Nik Mohamad Harith Nik Najib - Nik Najib, Nik Mohamad Harith (2015)
In today’s world, we live in a world with full of advertising. Anywhere we go and every moment a day in our life, we must encounter at least one advertisement. From traditional advertising method for example Billboards, Newspapers, radio or magazines, adverting has evolved into something more complex and rich. Nowadays, with the fast growth of mobile phones usage especially among generation Y, companies of goods and services has taken this opportunity to advertise their products and services through this new medium for interactive marketing. According to Malaysian Communication and Multimedia Commission (MCMC) base on their research on hand phone users’ survey 2014, throughout all over Malaysia; the total number of mobile phone users in 2014 is 8.40 percent which are 4,164,237 users among 38,167, 300 users and this number keep increasing time by time. In Kelantan alone the number of mobile phone user base in 2014 is 4.6 percent which population base is 6.8 percent.